Saccharomyces boulardii protease inhibits Clostridium difficile toxin A effects in the rat ileum. - Castagliuolo, I (1996)
Saccharomyces boulardii, a nonpathogenic yeast, is effective in treating some patients with Clostridium difficile diarrhea and colitis. We have previously reported that S. boulardii inhibits rat ileal secretion in response to C. difficile toxin A possibly by releasing a protease that digests the intestinal receptor for this toxin (C. Pothoulakis, C. P. Kelly, M. A. Joshi, N. Gao, C. J. O'Keane, I. Castagliuolo, and J. T. LaMont, Gastroenterology 104: 1108-1115, 1993). The aim of this study was to purify and characterize this protease. S. boulardii protease was partially purified by gel filtration on Sephadex G-50 and octyl-Sepharose. The effect of S. boulardii protease on rat ileal secretion, epithelial permeability, and morphology in response to toxin A was examined in rat ileal loops in vivo. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the purified S. boulardii protease revealed a major band at 54 kDa. Pretreatment of rat ileal brush border (BB) membranes with partially purified protease reduced specific toxin A receptor binding (by 26%). Partially purified protease digested the toxin A molecule and significantly reduced its binding to BB membranes in vitro (by 42%). Preincubation of toxin A with S. boulardii protease inhibited ileal secretion (46% inhibition, P < 0.01), mannitol permeability (74% inhibition, P < 0.01), and histologic damage caused by toxin A. Thus, S. boulardii protease inhibits the intestinal effects of C. difficile toxin A by proteolysis of the toxin and inhibition of toxin A binding to its BB receptor. Our results may be relevant to the mechanism by which S. boulardii exerts its protective effects in C. difficile infection in humans.